EDUCATION IN SCALE OF OBLIGATION - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2009)
This article analyses the conception of obligation, which is the essential component of morals education. Obligation is derived not from the natural or public request, but from the various inborns. Classification of inborns is grounded on human structure: physic, psychic and spiritual. Proper ways and means should be developed that enable to turn inborns into obligation and responsibility for oneself, socium, culture. The direction of obligation is determined by the progress of the personality, nation, state and humanities development. The implementation of interaction between inborns and obligations facilitates all functions of education and strengthens behaviour and values of the personality.
Keywords: education; obligation; inborn; walues